IGF-1 abuse in sport: clinical and medico-legal aspects - Molinelli, A.; Bonsignore, A.; Cicconi, M.; Cioè, A.; Traverso, A. (The Journal of Sports Medicine and Physical Fitness, 2011)
The frequent revisions of prohibited substances list established by WADA are aimed at keeping up with those drugs that, being increasingly used in medicine and in sports, play on one side a therapeutic role and, on the other, a doping role. Among the various hormone substances widely used in sports, the authors draw particular attention on IGF-1, a growth factor that is rapidly widespreading among athletes. Moreover, IGF-1 diffusion is not exclusively correlated with the doping phenomenon, being various the pathological conditions that may require the therapeutic use of this substance. As a consequence, during pathologies or medical treatments of various nature, the athletes should be informed of the IGF-1 administration because, if they are not duly apprised, they risk undergoing unjust sanctions from the competent authority. In fact, the athlete is given the possibility of communicating, before using, he is taking a medication of the WADA list for therapeutic reasons by applying for a TUE (Therapeutic Use Exemption). If this application is accepted on certified clinical grounds, the athlete will be allowed to use that substance even during sports competitions. However, the IGF-1 detection in the athlete`s body shows, at the present state-of-art, two different problems: the first one has a technical character and concerns the differential diagnosis between the quantity of the physiologically produced substance and the quantity of the exogenously administrated substance; the second problem has an economic character and regards to the high cost of the analysis and, consecutively, the necessity of finding a well-equipped laboratory centre.